THE EFFECT OF LENDING, THIRD PARTY FUNDS, NUMBER OF BRANCH OFFICES AND NON-PERFORMING LOANS ON BANKING PROFITABILITY - Sri Widiyasumarlin; Sugeng Riadi (Aktiva : Jurnal Akuntansi dan Investasi, 2022)
The purpose of this research is to analyze the effect of Lending, Third Party Funds, Number of Branch Offices and Non-Performing Loans on banking profitability. This quantitative associative research uses conventional commercial banks as the population with the Book IV category in Indonesia for the 2012-2019, with secondary data type in the form of annual reports of banking companies. The method used to collect the sample of this research is purposive sampling, that is based on predetermined criteria, there are 5 banks in the Book IV category that match the specified criteria, namely BNI, BRI, BCA, Bank Mandiri and CIMB Niaga. This study uses panel data regression analysis techniques. The results of this study indicate that partially lending has no effect on profitability. Variable Third Party Funds has no effect on profitability. Variable Number of Branch Offices has a positive effect on profitability. The Non-Performing Loan variable has a negative effect on banking profitability at Conventional Commercial Banks (Book IV Category)